Family Socioeconomic Status and Learning Engagement in Chinese Adolescents: The Multiple Mediating Roles of Resilience and Future Orientation - Chen, Jing-Jing; Jiang, Ting-Na; Liu, Ming-Fei (Frontiers in Psychology, 2021)
This study explored the mediating effects of resilience and future orientation on the relationship between family socioeconomic status (SES) and learning engagement within the context of Chinese culture based on the cognitive theory of social class. A total of 1,245 junior high school students were recruited to complete anonymous questionnaires regarding the objective and subjective SES of their families, resilience, future orientation, and learning engagement. The mediating effects were tested by stepped multiple linear regression. Results indicated the following: (1) the relationships between objective and subjective SES, resilience, future orientation, and learning engagement was significantly positive; (2) resilience only mediated the relationship between subjective SES and learning engagement, whereas future orientation mediated the relationships between objective/subjective SES and learning engagement; (3) resilience and future orientation sequentially mediated the relationship between subjective SES and learning engagement. The current study contributes to a better understanding of how family SES influences adolescent academic performance from the perspective of adolescent cognitive abilities. In addition, this study provides implications for the prevention and intervention of academic performance of poor adolescents due to low SES.